Polemics Over the Resolution of Human Rights Violation in Indonesia - Tandry, Novita; Deddy Agusriadi; Zulfadly Siregar; Muhammad Juwanda Arif; Alief Farhan (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
The resolution of human rights violations in Indonesia is often a controversial and complex topic. This study aims to analyze the polemics over the settlement of human rights violations and resolution of human rights violations in Indonesia, by using the content analysis research method. This method allows researchers to explore and understand various perspectives that appear in mass media, official documents, and other relevant sources on this issue. In this study, the data collected included news articles, human rights reports, and official statements from government and non-government organizations. Through systematic analysis, this research identifies key themes, communication patterns, and public responses to policies to resolve human rights violations. The results of this research analysis contribute to the challenges and opportunities in resolving human rights violations in Indonesia and recommend strategic steps to improve the effectiveness of related policies. This research also has the potential to be a reference for other researchers interested in similar issues in a broader context. It also provides a deeper insight into how issues of human rights violations are perceived and communicated in society.